Malignant soft tissue sarcoma of the shoulder treated by surface mould brachytherapy boost in an adjuvant setting - Mukherji, Ashutosh; Sinnatamby, Mourougan (Journal of Contemporary Brachytherapy, 2017)
Purpose : Soft tissue sarcomas of the extremities account for half of all soft tissue sarcomas. Radiotherapy and surgery have been the standard modalities in the treatment of this type of cancer. Brachytherapy can be used as the sole therapy, if the target volume is localized and easily accessible. This work reports three cases of shoulder soft tissue sarcomas with positive deep resected margins, treated with a combination of external beam radiotherapy and surface mould brachytherapy boost technique. Material and methods : Between January and June 2014, three patients received brachytherapy with sites close to the shoulder, and post-surgery involved deep resected margins. Each mould was made on a base of thermoplastic, over which dental wax was coated and catheters implanted. The target volume was defined as the tissue covering the tumor bed with lateral margins of 2-2.5 cm and depth of 1-1.5 cm. Treatment planning was computed tomography- based and dose prescribed was 85-100% isodose. Treatments has been delivered twice daily, six hours interval, and a review of reactions evaluated. Results : Volume receiving more than 150% of the prescribed dose has been limited to less than 2%, and that above 200% to be inside the mould. Brachytherapy equivalent dose at 2 Gy per fraction (EQD2) of these patients was 24 and 28.6 Gy. Maximum dose to organ at risk (OAR) (2 cc of OAR) ranged between 55-87% of prescribed dose, with a median dose being 80%. All cases had only grade 1 post-radiotherapy skin immediate reactions, which resolved within four weeks. In all patients, no treatment failures were noted at nearly 2-years post-irradiation. Conclusions : Surface mould brachytherapy in soft tissue sarcomas could be a useful alternative to interstitial brachytherapy, especially where the target volume is superficially extensive with underlying critical structures, and where catheter placement may be difficult, such as the shoulder.